2013
DOI: 10.1080/10401334.2013.827974
|View full text |Cite
|
Sign up to set email alerts
|

Medical Spanish Programs in the United States: A Critical Review of Published Studies and a Proposal of Best Practices

Abstract: There is a significant need for effective medical Spanish programs based on solid SLA principles and research methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 30 publications
0
30
1
Order By: Relevance
“…4 The finding that medical Spanish courses vary considerably regarding teaching modalities and instructor qualifications is consistent with a review by Hardin and Hardin in 2013, in which the authors reviewed 23 published studies of medical Spanish curricula. 39…”
Section: Resultsmentioning
confidence: 99%
“…4 The finding that medical Spanish courses vary considerably regarding teaching modalities and instructor qualifications is consistent with a review by Hardin and Hardin in 2013, in which the authors reviewed 23 published studies of medical Spanish curricula. 39…”
Section: Resultsmentioning
confidence: 99%
“…Medical students are often placed in situations where they must care for limited English proficient (LEP) patients [1]. As medical students prepare for residency training and independent practice, they must face the prospect of the growing LEP patient population juxtaposed with the lack of linguistically appropriate services at many medical centers.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that provider-patient language concordance leads to improved health outcomes [6], reduced medical errors of significance [7], and improved patient satisfaction [8]. Despite the increasing need for culturally and linguistically competent physicians [9, 10], and the student and institutional demand for Spanish language education, there is currently no standardized curriculum that addresses students’ Spanish skills in U.S. medical schools, including performance-based assessments of non-English-speaking patient encounters [1, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…University language courses play a crucial role in promoting “what counts” as medical language, and thus, it is fundamental for medical schools to develop alliances with critical language scholars who can help students (and more often than not, faculty members) debunk the notion that the so-called academic language is the only way to convey scientific notions. Therefore, institutions can help keep medical language education up to date with evolving local, regional, national, and global linguistic realities by promoting collaborative educational research and team-teaching between professionals in medicine and those in applied linguistics [ 18 ] and by regularly assessing specific outcomes measures [ 19 ], including faculty and learner attitudes and ideologies with regards to combining community vernaculars—such as the so called Spanglish, Chinglish and Hinglish, as well as regionalisms of health-related terms—into patient communication.…”
Section: Integration Of Translanguaging In Medical Education Settingsmentioning
confidence: 99%